Histopathological Spectrum of Diseases in Endometrial Biopsies: A Study of 250 Patients - Farzana Sarwar, Laila Zaib, Nazneen Iqbal, Shams ur Rehman, Qamoos Razzaq, Jamshed Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The endometrium undergoes various pathological changes due to hormonal fluctuations, infections, and malignant transformations. Histopathological examination of endometrial biopsies is crucial for diagnosing these diseases. Objective: To evaluate the histopathological spectrum of diseases observed in endometrial biopsies and to assess their clinical relevance in 250 patients. Methods: A retrospective study was conducted on 250 patients who underwent endometrial biopsies between July 2022 and June 2023. The biopsies were categorized based on histopathological findings into normal, benign, premalignant, and malignant lesions. Data analysis was performed using descriptive statistics and logistic regression to assess the correlation of age, clinical presentation, and histopathological diagnosis. Results: Among the 250 patients, 45% had normal endometrium, 35% had benign conditions, 10% had premalignant lesions, and 10% had malignant lesions. Logistic regression analysis revealed that age significantly correlated with the presence of malignant lesions (p < 0.05). Conclusion: Endometrial biopsy is essential for early detection of premalignant and malignant lesions, which improves patient outcomes. Early intervention, particularly in postmenopausal women, is critical. Keywords: Endometrial biopsy, histopathology, endometrial carcinoma, hyperplasia, premalignant, malignant lesions, uterine pathology.